Estimating the Willingness of Urban Residents in Savannakhet Province to Pay for the Dongnatad Protected Area Conservation - TOUNMANYSONE, Thongsa; BANMANIVONG, Lidsada; VONGKEO, Somphone; THONLAMEE, Keovilay; CHOUNLAMOUNTRY, Lattanamany; LALAIMTHAVISAY, Duangphachan (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objective of this study is to estimate the Willingness to Pay (WTP) of the urban residents in Savannakhet Province for the Dongnatad Protected Area (DPA) Conservation and seeks to identify the factors affecting WTP for the DPA Conservation. The willingness to pay was estimated by Contingent Valuation Method (CVM) approach through a close-ended questionnaire in Single Bound Dichotomous Choice (SBDC). The interview was conducted by face to face; the Logistic regression was applied to analyze data, the data came from random sampling in urban residents at Savannakhet Province and based on 400 samples. The results show a mean WTP of 7,459.73 kip per household per month. Multiplying this value to the total number of households in Kaisone-Phomvihan City, Savannakhet Province would give a total value of 160,272,299 kip/month. The significant factors as an influence the willingness to pay ranging from education, period of living, because it has statistically positive impact on WTP. Conversely, the number of family members and bids have statistically negative impact on WTP. These results offer information to policy makers for the forestry, wildlife and biodiversity conservation in DPA to sustainability in the future.